Frequency of musculoskeletal disorders in workers of a refinery from Lima, 2017 - Ramírez-Pozo, Egle Guisela (2019)
Introduction: It is estimated that musculoskeletal disorders represent the most frequent pathology in workers and is the cause of more days not worked due to disability. Objective: To determine the frequency of musculoskeletal disorders in workers of a refinery in Lima during the year 2017. Methods: A cross-sectional study. The demographic data and the registry of the diagnosis of musculoskeletal disorder, was based on results of imaging tests and clinical evaluation performed by a specialist, which was obtained through the review of occupational clinical records. Results: The sample included 223 workers and the frequency of musculoskeletal disorders was 52,9%; the most frequent musculoskeletal disorders were low back pain associated with herniated disc (25,1%), low back pain (13,4%), rotator cuff syndrome (5,8%) and neck pain with herniated disc (3,6 %). Conclusions: There is a high prevalence of musculoskeletal disorders in the trunk and upper extremities.